Serological, molecular and bacteriological approaches for detecting Leptospira sp. carrier rams maintained in semiarid conditions - Soares, Rafael Rodrigues; Barnabé, Nathanel Natércio da Costa; Nogueira, Denise Batista; da Silva, Laís Samara Cavalcante; Júnior, João Pessoa Araújo [UNESP]; Malossi, Camila Dantas [UNESP]; Ullmann, Leila Sabrina [UNESP]; da Costa, Diego Figueiredo; Silva, Maria Luana Cristiny Rodrigues; dos Santos Higino, Severino Silvano; de Azevedo, Sergio Santos; Alves, Clebert José (Elsevier, 2021)
Even in the adverse environmental conditions of the semiarid region, leptospires can survive and spread by alternative routes of transmission, such as sexual in ewes, however, there is no data on rams. Thus, the present study aimed to evaluate the use of serological, molecular and microbial tools applied to diagnosis of Leptospira sp. Infection in rams maintained in semiarid conditions. Biological samples of urinary (urine, kidney and bladder) and genital (vas deferens, epididymis tail and vesicular gland) tracts were collected from 40 slaughtered rams for polymerase chain reaction (PCR) and bacterial isolation, as well as blood samples for antibody detection through microscopic serum agglutination test (MAT). Anti-Leptospira antibodies were found in five (12.5%) animals with antibody titer of 50 and 2 (5%) for the titer 100 for serogroups Pyrogenes, Ballum, Icterohaemorrhagiae and Australis. Leptospira sp. DNA was found in PCR of organs and urine of 30 (75%) animals. Overall, 240 fragments of organs from the urinary and genital tracts and urine were evaluated, with 93 (38.7%) positive samples, being 48/120 (40%) for the urinary tract and 45/120 (37.5%) for the genital. There was no statistically significant difference between the tracts. A bladder sample was sent for sequencing and showed 99% similarity with L. interrogans. Of the 240 cultures evaluated, 59 (24.5%) had leptospire growth, being that 23 (39%) were confirmed in PCR. Considering the PCR of organs and urine and bacterial growth as gold standards, the cut-off 50 in MAT showed greater sensitivity when compared to cut-off 100, regardless of the material used. The great proportion of leptospiral DNA in organs, urine and culture and bacterial growth from the genital tracts reinforce its importance as an extra-renal site and highlights the possible role of rams in venereal transmission, as well as the sensitivity of the cut-off 50 suggested its adoption in the serology of rams maintained in semiarid conditions.
Keywords: Animal leptospirosis; Cut-off 50; Epidemiology; Genital leptospirosis; Molecular detection; Small ruminants